Effectiveness of Electronic Teaching Materials Using the Value Clarification Technique Approach in Elementary Schools - Maryani, Mila; Reinita, Reinita (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
The Indonesian government has taken professional competence, the ability to think creatively and learn new things, and fluency with modern forms of communication, information, and technology as its guiding principles. The Indonesian government has made information and technology proficiency a cornerstone of modern education. With the help of technical advancements in learning media, the area of education benefits from the use of technology that may facilitate the learning process. In primary schools, this research will use the Value Clarification Technique approach matrix model to find out how effective electronic teaching resources are for Pancasila Elements. The final output is a set of electronic teaching materials that have undergone rigorous validity testing by three different sets of specialists: material scientists, linguists, and media specialists. This study used a one-group Pretest-Posttest design, which is common in pre-experimental research. Thirteen women and twelve men made up the total of twenty-five participants in this research, which included both instructors and pupils. A test is the tool that this study use. Wilcoxon test and N-Gain value calculation are the data analysis techniques used. According to the study's findings, students in fourth grade at an elementary school that used electronic teaching materials based on the Value Clarification Technique approach matrix model learned more about Pancasila components.